Identification of two biological subgroups of complex regional pain syndrome type 1 by transcriptomic profiling of skin and blood in women - Melina Pérez Vertti Valdés; Astrid Jüngel; Pamela Bitterli; Jan Devan; Hubert Rehrauer; Lennart Opitz; Laura Sirucek; Petra Schweinhardt; Sabrina Catanzaro; Oliver Distler; Florian Brunner; Stefan Dudli (Molecular Medicine)
Abstract Background Patients with Complex Regional Pain Syndrome (CRPS) present prolonged, debilitating pain and functional impairment. Treatments are not disease-modifying due to the poorly understood underlying pathomechanisms. This study aimed to identify the molecular signatures of potential CRPS type 1 subgroups. Methods Twelve women with CRPS type 1 were included. Demographics and pain questionnaires were recorded. Skin biopsies of the affected and non-affected limbs (n = 6 + 6) and peripheral blood (n = 11) were collected. RNA sequencing was performed on skin and peripheral blood mononuclear cells (PBMCs). Twenty cytokines were quantified in blood plasma (n = 12). Results Cluster analysis of the affected skin identified two CRPS subgroups (SG). SG1 exhibited increased gene expression related to epidermal development, metabolic processes, and a greater abundance of keratinocytes. SG2 showed enhanced transcriptomic changes in inflammatory, immune, and fibrotic processes, along with higher abundance of fibroblasts, macrophages, and endothelial cells. PBMCs transcriptomics revealed the same SG1/SG2 clusters and highlighted a stronger inflammatory response in the blood of SG1, suggesting distinct tissue-specific immune responses for the subgroups. Interleukin-1 receptor antagonist (IL-1RA) levels were higher in the blood plasma of SG1 (FDR = 0.01), consistent with its encoding gene IL1RN expression in PBMCs (log2 FC = 1.10, P < 0.001) and affected skin (log2 FC = 0.88, P = 0.006). Subgroups did not differ in demographic or clinical parameters but correlations among clinical factors varied between them. Conclusions This study identified two potential biological subgroups of CRPS type 1 in women through skin and blood transcriptomic profiling, advancing the understanding of this condition. This could facilitate the development of targeted treatments for CRPS type 1.